Hadith #4918 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Kulthum bint 'Uqba (Sunan Abi Dawud)
The Prophet (ﷺ) said: The believer is the believer’s mirror, and the believer is the believer’s brother who guards him against loss and protects him when he is absent.
Grade: Hasan